Climate resilient food safety net basins for dryland restoration in Eastern Africa - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
Evaluation of data collected from nearly 2000 farm households trialing and adapting different planting basin designs to their local circumstances, facilitated by innovation platforms known as communities of practice, demonstrates their utility as a food safety net.